01.06.2015 Views

Chapter 3 Interpolation and Polynomial Approximation

Chapter 3 Interpolation and Polynomial Approximation

Chapter 3 Interpolation and Polynomial Approximation

SHOW MORE
SHOW LESS

You also want an ePaper? Increase the reach of your titles

YUMPU automatically turns print PDFs into web optimized ePapers that Google loves.

<strong>Chapter</strong> 3<br />

<strong>Interpolation</strong> <strong>and</strong> <strong>Polynomial</strong><br />

<strong>Approximation</strong><br />

Let x 0 , x 1 ,..., x n be distinct real <strong>and</strong> y 0 , y 1 ,..., y n be associated function values. We will<br />

find a polynomial p(x) that interpolates the given data:<br />

p(x i ) = y i ,<br />

i = 0, 1,...,n.<br />

3.1 <strong>Interpolation</strong> <strong>and</strong> Lagrange <strong>Polynomial</strong><br />

Theorem 3.1 Given n + 1 distinct points x 0 , x 1 ,..., x n <strong>and</strong> n + 1 ordinates y 0 , y 1 ,...,<br />

y n , there is a polynomial p(x) of degree ≤ n that interpolates y i at x i , i = 0, 1,...,n. This<br />

polynomial p(x) is unique among the set of all polynomials of degree at most n.<br />

proof : (1) Existence: Denote the Lagrange interpolation polynomial<br />

( )<br />

n∑<br />

n∏ x − xi<br />

p(x) = y j l j (x), l j (x) =<br />

.<br />

x j − x i<br />

j=0<br />

i=0,i≠j<br />

The polynomial p(x) with degree ≤ n satisfies p(x i ) = y i , i = 0, 1,...,n, since l j (x i ) = 0<br />

if i ≠ j <strong>and</strong> l j (x i ) = 1 if i = j.<br />

(2) Uniqueness: Suppose q(x) is another polynomial of degree ≤ n satisfying<br />

q(x i ) = y i ,<br />

i = 0, 1,...,n.<br />

Define r(x) = p(x) − q(x), then degree r(x) ≤ n <strong>and</strong><br />

r(x i ) = p(x i ) − q(x i ) = 0,<br />

i = 0, 1,...,n.<br />

1


Since r(x) has n + 1 zeros, we must have r(x) ≡ 0. Thus p(x) = q(x). This completes<br />

the proof of theorem.<br />

Theorem 3.2 Let x 0 , x 1 ,..., x n be distinct number in [a,b] <strong>and</strong> f(x) ∈ C n+1 [a,b]. Then<br />

there exists x ∈ [a,b] <strong>and</strong> ξ(x) ∈ (a,b) with<br />

f(x) −<br />

n∑<br />

j=0<br />

f(x j )l j (x) = (x − x 0)...(x − x n )<br />

f (n+1) (ξ(x)).<br />

(n + 1)!<br />

proof : Assume x does not equal any node point. Since if x is any node point it is<br />

trivially true. Define<br />

n∑<br />

E(x) = f(x) − p n (x), p n (x) = f(x j )l j (x)<br />

j=0<br />

G(t) = E(t) − Φ(t)<br />

Φ(x) E(x), Φ(x) = (x − x 0)....(x − x n )<br />

The function G(t) ∈ C n+1 [a,b]. Also<br />

G(x i ) = E(x i ) − Φ(x i)<br />

E(x) = 0,<br />

Φ(x)<br />

G(x) = E(x) − E(x) = 0<br />

i = 0, 1,...,n<br />

Thus G has n + 2 distinct zeros in [a,b]. Using the mean value theorem, G (j) (t) has<br />

n + 2 − j zeros, for j = 0, 1,...,n + 1. Let ξ be a zero of G (n+1) (t).<br />

G (n+1) (t) = f (n+1) (t) −<br />

(n + 1)!<br />

Φ(x) E(x)<br />

G (n+1) (ξ) = f (n+1) (ξ) −<br />

(n + 1)!<br />

Φ(x) E(x) = 0<br />

E(x) =<br />

This completes the proof of theorem.<br />

Φ(x)<br />

(n + 1)! f(n+1) (ξ)<br />

2


3.2 Divided Difference<br />

Newton’s divided difference formula for the interpolation polynomial:<br />

p 0 (x) = f(x 0 )<br />

p j (x) = p j−1 (x) + (x − x 0 )...(x − x j−1 )f[x 0 ,x 1 ,...,x j ], j = 1, 2,...,n<br />

The coefficient a n = f[x 0 ,x 1 ,...,x n ] is called the n-th-order Newton divided difference of<br />

f(x). Define<br />

f[x 0 ,x 1 ,...,x n ] = f[x 1,...,x n ] − f[x 0 ,x 1 ,...,x n−1 ]<br />

x n − x 0<br />

Lemma 3.1 The n-th-order Newton divided difference have the following theory.<br />

1. Let Φ n (x) = (x − x 0 )...(x − x n ). Then the coefficient a n can be formed as:<br />

f[x 0 ,x 1 ,...,x n ] =<br />

2. For any permutation (i 0 ,...,i n ) of (0, 1,...,n)<br />

n∑<br />

j=0<br />

f(x j )<br />

Φ ′ n(x j )<br />

f[x 0 ,x 1 ,...,x n ] = f[x i0 ,x i1 ,...,x in ]<br />

3. Let f(x) be enough smooth.<br />

f[x 0 ,x 1 ,...,x m ] = f(m) (ξ)<br />

, ξ ∈ ϑ{x 0 ,...,x m } (3.2.1)<br />

m!<br />

Moreover, if x 0 = x 1 = ... = x n then f[x 0 ,x 1 ,...,x n ] = f (n) (x 0 )/n!.<br />

4. Suppose f(x) be enough smooth.<br />

proof :<br />

d<br />

dx f[x 0,x 1 ,...,x n ,x] = f[x 0 ,x 1 ,...,x n ,x,x]<br />

p n (x) = p n−1 (x) + (x − x 0 )...(x − x n−1 )f[x 0 ,x 1 ,...,x n ]<br />

If x is not a node point, we have Lagrange interpolation polynomial<br />

p n (x) =<br />

n∑<br />

j=0<br />

Φ n (x)<br />

(x − x j )Φ ′ n(x j ) · f(x j) (3.2.2)<br />

3


By looking at each n-th-degree term in (3.2.2), we obtain<br />

This completes the proof of (1).<br />

f[x 0 ,x 1 ,...,x n ] =<br />

n∑<br />

j=0<br />

f(x j )<br />

Φ ′ n(x j )<br />

n∑<br />

j=0<br />

f(x j )<br />

n<br />

Φ ′ n(x j ) = ∑ f(x ij )<br />

Φ ′ n(x ij )<br />

Then f[x 0 ,x 1 ,...,x n ] = f[x i0 ,x i1 ,...,x in ]. This completes the proof of (2).<br />

j=0<br />

p n+1 (x) = p n (x) + (x − x 0 )...(x − x n )f[x 0 ,...,x n ,t], p n+1 (t) = f(t)<br />

By Theorem 3.2 we have<br />

Let t = x n+1 , n = m − 1 then<br />

This completes the proof of (3).<br />

f(t) − p n (t) = (t − x 0 )...(t − x n )f[x 0 ,...,x n ,t]<br />

f[x 0 ,...,x n ,t] = f(n+1) (ξ)<br />

(n + 1)!<br />

f[x 0 ,...,x m ] = f(m) (ξ)<br />

m!<br />

d<br />

dx f[x f[x 0 ,x 1 ,...,x n ,x + h] − f[x 0 ,x 1 ,...,x n ,x]<br />

0,x 1 ,...,x n ,x] = lim<br />

h→0 h<br />

f[x 0 ,x 1 ,...,x n ,x + h] − f[x,x 0 ,x 1 ,...,x n ]<br />

= lim<br />

h→0 (x + h) − x<br />

= f[x,x 0 ,x 1 ,...,x n ,x] = f[x 0 ,x 1 ,...,x n ,x,x]<br />

This completes the proof of (4).<br />

= lim<br />

h→0<br />

f[x,x 0 ,x 1 ,...,x n ,x + h]<br />

Theorem 3.3 (Hermite-Gennochi) Let x 0 , x 1 ,..., x n be distinct <strong>and</strong> f(x) ∈ C n on<br />

ϑ{x 0 ,...,x n }. Then<br />

∫ ∫<br />

f[x 0 ,...,x n ] = ... f (n) (t 0 x 0 + ... + t n x n )dt 1 ...dt n<br />

τ n<br />

4


where<br />

τ n =<br />

{<br />

(t 1 ,...,t n )| ∀ t i ≥ 0,<br />

}<br />

n∑<br />

n∑<br />

t i ≤ 1 , t 0 = 1 − t i .<br />

i=1<br />

i=1<br />

proof : We show that it is true for n = 1 <strong>and</strong> n = 2.<br />

(1) n = 1. Then τ 1 = [0, 1] <strong>and</strong> t 0 = 1 − t 1<br />

=<br />

∫ 1<br />

0<br />

f ′ (t 0 x 0 + t 1 x 1 )dt 1 =<br />

∫ 1<br />

1<br />

f(x 0 + t 1 (x 1 − x 0 ))<br />

∣<br />

x 1 − x 0<br />

0<br />

f ′ (x 0 + t 1 (x 1 − x 0 ))dt 1<br />

t 1 =1<br />

t 1 =0<br />

= f(x 1) − f(x 0 )<br />

x 1 − x 0<br />

= f[x 0 ,x 1 ]<br />

(2) n=2. Then τ 2 is the triangle with vertices (0, 0), (0, 1) <strong>and</strong> (1, 0).<br />

=<br />

=<br />

=<br />

=<br />

∫ ∫<br />

τ 2<br />

f ′′ (t 0 x 0 + t 1 x 1 + t 2 x 2 )dt 1 dt 2<br />

∫ 1 ∫ 1−t1<br />

0<br />

∫ 1<br />

0<br />

f ′′ (x 0 + t 1 (x 1 − x 0 ) + t 2 (x 2 − x 0 ))dt 2 dt 1<br />

0<br />

1<br />

[f ′ t 2 =1−t 1<br />

(x 0 + t 1 (x 1 − x 0 ) + t 2 (x 2 − x 0 ))]<br />

∣ dt 1<br />

x 2 − x 0 t 2 =0<br />

∫<br />

1<br />

1<br />

]<br />

f ′ (x 2 + t 1 (x 1 − x 2 ))dt 1 − f ′ (x 0 + t 1 (x 1 − x 0 ))dt 1<br />

[∫ 1<br />

x 2 − x 0 0<br />

1<br />

x 2 − x 0<br />

{f[x 1 ,x 2 ] − f[x 1 ,x 0 ]} = f[x 0 ,x 1 ,x 2 ]<br />

This completes the proof of theorem.<br />

• Forward difference <strong>and</strong> backward difference<br />

Let the note points x i = x 0 +ih, i=0,1,2,3,.... Then define the forward difference operator<br />

△:<br />

△f(x i ) = f(x i+1 ) − f(x i )<br />

0<br />

△ r+1 f(z) = △ r f(z + h) − △ r f(z),<br />

△ 0 f(z) = f(z).<br />

The term △ r f(z) is the rth-order forward difference of f at z.<br />

Lemma 3.2<br />

f[x 0 ,x 1 ,...,x k ] = 1<br />

k!h k △k f 0 , k ≥ 0.<br />

5


proof : For k = 0, it is trivially true. For k = 1,<br />

f[x 0 ,x 1 ] = f(x 1) − f(x 0 )<br />

x 1 − x 0<br />

= 1 h △ f 0.<br />

Assume the result is true for all k ≤ r. Then for k = r + 1<br />

f[x 0 ,x 1 ,...,x r+1 ] = f[x 1,...,x r+1 ] − f[x 0 ,x 1 ,...,x r ]<br />

x r+1 − x 0<br />

[<br />

1 1<br />

=<br />

(r + 1)h r!h r △r f 1 − 1 ]<br />

r!h r △r f 0<br />

1<br />

=<br />

(r + 1)!h r+1 △r+1 f 0<br />

This completes the proof of lemma.<br />

Lemma 3.3<br />

△ r f(x i ) = h r f (r) (ξ i ), x i ≤ ξ i ≤ x i+r .<br />

proof : By (3.2.1) <strong>and</strong> Lemma 3.2 we obtain<br />

△ r f(x i ) = r!h r f[x i ,x i+1 ,...,x i+r ] = r!h rf(r) (ξ i )<br />

r!<br />

This completes the proof of lemma.<br />

= h r f (r) (ξ i ).<br />

From Lemma 3.2 we have the Newton forward difference form of the interpolating polynomial<br />

n∑<br />

p n (x) = f 0 + (x − x 0 )...(x − x k−1 )f[x 0 ,...,x k ]<br />

k=1<br />

n∑<br />

= f 0 + (x − x 0 )...(x − x k−1 ) 1<br />

k=1<br />

k!h k △k f 0<br />

( )<br />

n∑ µ<br />

=<br />

△ k f<br />

k 0 , µ = x − x 0<br />

.<br />

k=0<br />

h<br />

Define the binomial coefficients,<br />

( )<br />

µ µ(µ − 1)...(µ − k + 1)<br />

= , k > 0,<br />

k<br />

k!<br />

Define the backward difference by<br />

▽f(z) = f(z) − f(z − h)<br />

(<br />

µ<br />

0<br />

)<br />

= 1.<br />

▽ r+1 f(z) = ▽ r f(z) − ▽ r f(z − h), r ≥ 1.<br />

6


And we obtain the Newton backward difference form of the interpolating polynomial<br />

with the notes x 0 , x −1 , ..., x −n , <strong>and</strong> x −j = x 0 − jh<br />

p n (x) =<br />

( )<br />

n∑ µ<br />

j<br />

j=0<br />

▽ j f 0 , µ = x − x 0<br />

.<br />

h<br />

3.3 Hermite <strong>Interpolation</strong><br />

The Hermite interpolation polynomial p(x) of f(x) with the distinct notes x 1 , x 2 ,..., x n<br />

satisfies<br />

p(x i ) = f(x i ) = y i , p ′ (x i ) = f ′ (x i ) = y ′ i, i = 1, 2,...,n.<br />

Then the polynomial p(x) is existence <strong>and</strong> uniqueness with degree ≤ 2n − 1.<br />

• The Newton divided difference form<br />

p 2n−1 (x) = f(x 1 ) + (x − x 1 )f[x 1 ,x 1 ] + (x − x 1 ) 2 f[x 1 ,x 1 ,x 2 ] + ...<br />

+ (x − x 1 ) 2 (x − x 2 ) 2 ...(x − x n )f[x 1 ,x 1 ,...,x n ,x n ]<br />

• Example<br />

f(x) − p 2n−1 (x) = (x − x 1 ) 2 (x − x 2 ) 2 ...(x − x n ) 2 f[x 1 ,x 1 ,...,x n ,x n ,x]<br />

1. Find p ∈ P 3 such that p(x 0 ) = f 0 , p ′ (x 0 ) = f ′ 0, p ′′ (x 0 ) = f ′′<br />

0 , p ′′′ (x 0 ) = f ′′′<br />

0 .<br />

x f<br />

x 0 f 0<br />

x 0 f 0 f 0<br />

′<br />

x 0 f 0 f 0<br />

′<br />

x 0 f 0 f 0<br />

′<br />

1<br />

f ′′<br />

2 0<br />

1<br />

f ′′<br />

2 0<br />

1<br />

f ′′′<br />

6 0<br />

Then the diagonal entries are the coefficients of the power series:<br />

p(x) = f 0 + f ′ 0(x − x 0 ) + 1 2 f ′′<br />

0 (x − x 0 ) 2 + 1 6 f ′′′<br />

0 (x − x 0 ) 3<br />

which is the Taylor polynomial of degree 3.<br />

2. Find p ∈ P 3 such that p(x 0 ) = f 0 , p(x 1 ) = f 1 , p ′ (x 1 ) = f ′ 1, p(x 2 ) = f 2 .<br />

7


x f<br />

x 0 f 0<br />

x 1 f 1 f[x 0 ,x 1 ]<br />

x 1 f 1 f 1 ′ f[x 0 ,x 1 ,x 1 ]<br />

x 2 f 2 f[x 1 ,x 2 ] f[x 1 ,x 1 ,x 2 ] f[x 0 ,x 1 ,x 1 ,x 2 ]<br />

If denote the diagonal entries as before by a 0 , a 1 , a 2 , a 3 , Newton’s formula takes<br />

the form:<br />

p(x) = a 0 + a 1 (x − x 0 ) + a 2 (x − x 0 )(x − x 1 ) + a 3 (x − x 0 )(x − x 1 ) 2<br />

Then the error formula becomes<br />

f(x) − p(x) = (x − x 0 )(x − x 1 ) 2 (x − x 2 )f[x 0 ,x 1 ,x 1 ,x 2 ,x]<br />

= (x − x 0 )(x − x 1 ) 2 (x − x 2 ) f(4) (ξ)<br />

, ξ ∈ [x 0 ,x 2 ]<br />

4!<br />

8


3.4 Cubic spline <strong>Interpolation</strong><br />

Consider a function f defined on [a,b] <strong>and</strong> a = x 0 < x 1 < ... < x n = b, we say S(x) is a<br />

cubic spline interpolant if it satisfies the following conditions:<br />

(1) S(x) is a cubic polynomial denoted S j (x) on [x j ,x j+1 ], j = 0, 1,...,n − 1.<br />

(2) S(x j ) = f(x j ), j = 0, 1,...,n.<br />

(3) S j+1 (x j+1 ) = S j (x j+1 ), j = 0, 1,...,n − 2.<br />

(4) S ′ j+1(x j+1 ) = S ′ j(x j+1 ), j = 0, 1,...,n − 2.<br />

(5) S ′′<br />

j+1(x j+1 ) = S ′′<br />

j (x j+1 ), j = 0, 1,...,n − 2.<br />

(6) One of the following boundary conditions is satisfied<br />

(i) Natural boundary conditions: S ′′ (x 0 ) = S ′′ (x n ) = 0.<br />

(ii) Clamped boundary conditions: S ′ (x 0 ) = f ′ (x 0 ) <strong>and</strong> S ′ (x n ) = f ′ (x n ).<br />

Note: The cubic spline interpolation S(x) has 4n undetermined coefficients <strong>and</strong> satisfies<br />

(n+1)+3(n−1) = 4n−2 condition equations then it must add two boundary conditions,<br />

natural boundary conditions or clamped boundary conditions.<br />

To construct the cubic spline interpolant for a given function f(x) satisfying the<br />

conditions (1)−(6). First, let x ∈ [x j ,x j+1 ], x j+1 − x j = h j <strong>and</strong><br />

S j (x) = a j + b j (x − x j ) + c j (x − x j ) 2 + d j (x − x j ) 3 , j = 0, 1,...,n − 1.<br />

From the condition (2), we obtain<br />

a j = f(x j ), j = 0, 1,...,n − 1.<br />

Defined a n = f(x n ). From the condition (3), we obtain the equations<br />

a j+1 = a j + b j h j + c j h 2 j + d j h 3 j, j = 0, 1,...,n − 1. (3.4.1)<br />

Defined b n = S ′ (x n ) <strong>and</strong> observed that S ′ j(x) = b j + 2c j (x − x j ) + 3d j (x − x j ) 2 . From the<br />

condition (4), we obtain the equations<br />

b j+1 = b j + 2c j h j + 3d j h 2 j, j = 0, 1,...,n − 1. (3.4.2)<br />

Defined c n = S ′′ (x n )/2 <strong>and</strong> observed that S ′′<br />

j (x) = 2c j + 6d j (x − x j ). From the condition<br />

(5), we obtain the equations<br />

c j+1 = c j + 3d j h j , j = 0, 1,...,n − 1.<br />

9


Then<br />

d j = 1<br />

3h j<br />

(c j+1 − c j ), j = 0, 1,...,n − 1. (3.4.3)<br />

Substituting the value, d j , into (3.4.1) <strong>and</strong> (3.4.2) gives the new equations<br />

a j+1 = a j + b j h j + h2 j<br />

3 (2c j + c j+1 ), j = 0, 1,...,n − 1, (3.4.4)<br />

From the equation (3.4.4), we obtain<br />

b j+1 = b j + h j (c j + c j+1 ), j = 0, 1,...,n − 1. (3.4.5)<br />

b j = 1 h j<br />

(a j+1 − a j ) − h j<br />

3 (2c j + c j+1 ), j = 0, 1,...,n − 1. (3.4.6)<br />

Substituting these values into the equation (3.4.5), when the index is reduced by 1, gives<br />

the linear system of equations<br />

⇒<br />

b j = b j−1 + h j−1 (c j−1 + c j )<br />

1 (a j+1 − a j ) − h j<br />

h j 3 (2c j + c j+1 )<br />

= 1<br />

h j−1<br />

(a j − a j−1 ) − h j−1<br />

3 (2c j−1 + c j ) + h j−1 (c j−1 + c j )<br />

⇒ h j−1 c j−1 + 2(h j−1 + h j )c j + h j c j+1 = 3 h j<br />

(a j+1 − a j ) − 3<br />

h j−1<br />

(a j − a j−1 ) (3.4.7)<br />

for each j = 1,...,n − 1. The system (3.4.7) involves, as unknowns, only {c j } n j=0. Note<br />

that once the values of {c j } n j=0 are known, it is a simple matter to find the remainder<br />

values {b j } n−1<br />

j=0 from Eq. (3.4.6) <strong>and</strong> {d j } n−1<br />

j=0 from Eq. (3.4.3) <strong>and</strong> to construct the cubic<br />

polynomials {S j } n−1<br />

j=0.<br />

• Natural spline interpolant: S ′′ (x 0 ) = S ′′ (x n ) = 0.<br />

The boundary conditions imply that c n = S ′′ (x n )/2 = 0 <strong>and</strong><br />

0 = S ′′ (x 0 ) = 2c 0 + 6d 0 (x 0 − x 0 ) ⇒ c 0 = 0.<br />

10


The two equations c 0 = 0 <strong>and</strong> c n = 0 together with the equations in (3.4.7) produce a<br />

linear system described by AX = b, where A is the (n + 1) × (n + 1) matrix<br />

⎡<br />

A =<br />

⎢<br />

⎣<br />

1 0 0 · · · ... · · · · · · 0<br />

h 0 2(h 0 + h 1 ) h 1 0 · · · · · · · · · 0<br />

0 h 1 2(h 1 + h 2 ) h 2 0 · · · · · · 0<br />

.<br />

...<br />

...<br />

0 · · · · · · 0 h n−3 2(h n−3 + h n−2 ) h n−2 0<br />

0 · · · · · · · · · 0 h n−2 2(h n−2 + h n−1 ) h n−1<br />

0 · · · · · · · · · · · · 0 0 1<br />

...<br />

.<br />

⎤<br />

⎥<br />

⎦<br />

⎡<br />

b =<br />

⎢<br />

⎣<br />

0<br />

3<br />

h 1<br />

(a 2 − a 1 ) − 3 h 0<br />

(a 1 − a 0 )<br />

.<br />

3<br />

h n−1<br />

(a n − a n−1 ) − 3<br />

h n−2<br />

(a n−1 − a n−2 )<br />

0<br />

⎤<br />

⎥<br />

⎦<br />

⎡<br />

X =<br />

⎢<br />

⎣<br />

c 0<br />

c 1<br />

.<br />

c n−1<br />

c n<br />

⎤<br />

⎥<br />

⎦<br />

• Clamped spline interpolant: S ′ (x 0 ) = f ′ (x 0 ), S ′ (x n ) = f ′ (x n ).<br />

From the two boundary conditions, we obtain the following two equations:<br />

f ′ (x 0 ) = S ′ (x 0 ) = b 0 = 1 h 0<br />

(a 1 − a 0 ) − h 0<br />

3 (2c 0 + c 1 )<br />

⇒ 2h 0 c 0 + h 0 c 1 = 3 h 0<br />

(a 1 − a 0 ) − 3f ′ (a) (3.4.8)<br />

f ′ (x n ) = S ′ (x n ) = b n = b n−1 + h n−1 (c n−1 + c n )<br />

= 1 (a n − a n−1 ) − h n−1<br />

h n−1 3 (2c n−1 + c n ) + h n−1 (c n−1 + c n )<br />

= a n − a n−1<br />

h n−1<br />

+ h n−1<br />

3 (c n−1 + 2c n )<br />

⇒ h n−1 c n−1 + 2h n−1 c n = 3f ′ (b) − 3<br />

h n−1<br />

(a n − a n−1 ) (3.4.9)<br />

11


Equations (3.4.7), together with the equations (3.4.8) <strong>and</strong> (3.4.9) determine the linear<br />

system described by AX = b, where A is the (n + 1) × (n + 1) matrix<br />

⎡<br />

A =<br />

⎢<br />

⎣<br />

⎤<br />

2h 0 h 0 0 · · · · · · · · · · · · 0<br />

h 0 2(h 0 + h 1 ) h 1 0 · · · · · · · · · 0<br />

0 h 1 2(h 1 + h 2 ) h 2 0 · · · · · · 0<br />

.<br />

...<br />

...<br />

...<br />

.<br />

0 · · · · · · 0 h n−3 2(h n−3 + h n−2 ) h n−2 0<br />

⎥<br />

0 · · · · · · · · · 0 h n−2 2(h n−2 + h n−1 ) h n−1 ⎦<br />

0 · · · · · · · · · · · · 0 h n−1 2h n−1<br />

⎡<br />

b =<br />

⎢<br />

⎣<br />

3<br />

h 0<br />

(a 1 − a 0 ) − 3f ′ (a)<br />

3<br />

h 1<br />

(a 2 − a 1 ) − 3 h 0<br />

(a 1 − a 0 )<br />

.<br />

3<br />

h n−1<br />

(a n − a n−1 ) − 3<br />

h n−2<br />

(a n−1 − a n−2 )<br />

3f ′ (b) − 3<br />

h n−1<br />

(a n − a n−1 )<br />

⎤<br />

⎥<br />

⎦<br />

⎡<br />

X =<br />

⎢<br />

⎣<br />

c 0<br />

c 1<br />

.<br />

c n−1<br />

c n<br />

⎤<br />

⎥<br />

⎦<br />

Exercise 1. A natural cubic spline S on [0, 2] is defined by<br />

S(x) =<br />

{<br />

S0 (x) = 1 + 2x − x 3 , if 0 ≤ x < 1<br />

S 1 (x) = a + b(x − 1) + c(x − 1) 2 + d(x − 1) 3 , if 1 ≤ x ≤ 2<br />

Find a, b, c, d.<br />

Exercise 2. A clamped cubic spline S on [1, 3] is defined by<br />

S(x) =<br />

{<br />

S0 (x) = 3(x − 1) + 2(x − 1) 2 − (x − 1) 3 , if 1 ≤ x < 2<br />

S 1 (x) = a + b(x − 2) + c(x − 2) 2 + d(x − 2) 3 , if 2 ≤ x ≤ 3<br />

Given f ′ (1) = f ′ (3), find a, b, c, d.<br />

12

Hooray! Your file is uploaded and ready to be published.

Saved successfully!

Ooh no, something went wrong!